“New” State Actors and Conflict-Affected States: Confronting Violence, Shifting Ambitions, and Adjusting Principles - Paczyńska, Agnieszka (Frontiers in Political Science, 2021)
Over the past couple of decades, “new” state actors such as Brazil, China, Russia, India, Turkey and countries of the Arab Gulf among others, have been playing an increasingly prominent role in assistance provision to conflict-affected states. Skeptical of the liberal peacebuilding model, they have emphasized supporting economic development and avoided promoting political reforms, viewing them as too interventionist in domestic affairs of conflict-affected states. Rather, they have emphasized solidarity, cooperation, mutual support, respect for state sovereignty and are committed to non-intervention norms. However, the foreign policies of “new” state actors have been far from static. This article argues that these norms mask more complex relationships between “new” state actors and conflict-affected states. Historically, the “new” actors have tended to adhere less to non-intervention norm in their immediate neighborhood. Now, as they have become more deeply engaged with countries emerging out of violent conflict, have come to aspire to playing more prominent global roles, and the competition between them has risen, their adherence to principles of non-interference has come under strain and to policy shifts regarding issues of peace and security.